Money in the late Roman Republic - Hollander, David B. (David Bruce) (Columbia studies in the classical tradition ;, 2007)
Places coinage in its broader monetary context by examining the role of bullion, financial instruments, and commodities such as grain and wine in making payments and facilitating exchange Rome's monetary system. This book examines how the availability of such assets affected the demand for coinage and the development of the Republican economy.